Effects of praziquantel on early life stages of Grass carp, Ctenopharyngodon idella - Velisek, Josef; Strouhova, Alzbeta; Sandova, Marie; Zuskova, Eliska; Dvorak, Petr; Stara, Alzbeta (Veterinarni medicina, 2025)
This study aimed to assess the toxicity of the anthelmintic drug praziquantel in the early life stages of grass carp (Ctenopharyngodon idella). The toxicity was evaluated based on mortality, early ontogeny development, growth, oxidative stress biomarkers, antioxidant enzymes and histopathology. Praziquantel at all tested concentrations (1, 2, 4 and 6 mg/l) showed no significant adverse effects on the hatching of grass carp. Concentrations of 2, 4 and 6 mg/l praziquantel caused significantly (P < 0.01) higher mortality and slower growth compared with controls. Praziquantel at concentrations (4 and 6 mg/l) showed a significant (P < 0.01) delay of early ontogeny of grass carp. Concentration of 2 mg/l praziquantel caused significantly (P < 0.01) higher GST activity than controls. Among the groups, no histological changes were detected in tissues. For the early life of grass carp, praziquantel is safe at concentrations ≤1 mg/l.
Keywords: histopathology; antioxidant biomarkers; fish; antiparasitic drug; carp